The Improvement of Infant and Child Mortality Through Good Public Health Service in Lamandau Regency (International Journal of Religion, 2024)
Introduction: The Minimum Service Standards for Health mandate essential health services for all citizens, delivered through Puskesmas (Community et al.). Established in 1968, these centres aim to equalize health services across the country. Despite progress, challenges such as unequal access, insufficient healthcare workers, and limited facilities persist. Child health services, crucial for reducing mortality rates, have shown improvement, but disparities remain. Lamandau Regency, a new autonomous region in Central Kalimantan, illustrates the ongoing challenges in health development.Theoretical Review: The concept of public service in Indonesia is shaped by administrative, political, and legal dimensions, as articulated by Rosenbloom and Kravchuk (2005). This includes managerial decentralization, political representativeness, responsiveness, and legal accountability. Essential health services, integral to public services in Indonesia, are primarily delivered through Puskesmas, mandated by Minister of Health Regulation No. 75 of 2014 to prioritize promotive and preventive efforts at the primary level.Method: This study employs qualitative research to explore the social phenomenon of the health service system, utilizing an explanatory research approach to uncover causal networks.Result and Discussion: The Infant Mortality Rate (IMR) in Lamandau Regency decreased from 2015 to 2019, reflecting improvements in newborn health services. Puskesmas, like Bukit Jaya and Bayat, prioritize community partnership in service delivery, fostering responsibility and community involvement. This approach enhances service quality through two-way communication and community-driven initiatives like the Posyandu program. Staff adequacy at Bayat Puskesmas underscores the importance of local government support in health service.Conclusion: The decreasing Infant Mortality Rate (IMR) in Lamandau Regency suggests improved newborn health services.